Immunoregulatory Role of miRNA-26 in Modulating IL-32, IL-33, IL-34, and MMP-9 Expression in Rheumatoid Arthritis - AlChalabi, Rawaa; Al-Hammood, Orooba; A. Shaban, Semaa; Hameed Abbas, Saja (Al-Nahrain Journal of Science, 2025)
Rheumatoid arthritis (RA) is a systemic autoimmune illness marked by abnormal cytokine expression and persistent inflammation. MicroRNAs (miRNAs), particularly miRNA-26, have been implicated in the regulation of inflammatory pathways and show promise as potential biomarkers for RA diagnosis and treatment monitoring. Aim: This study aimed to evaluate miR-26 expression about established clinical markers and pro-inflammatory cytokines, to identify potential predictive markers of treatment response and contribute to more personalized management strategies in RA. Method: 180 participants were enrolled and categorized into three groups: Newly diagnosed RA patients (NDRA), biologically treated RA patients (TRA), and Healthy controls (HC). Each group consisted of 60 Individuals. The miR-26 expression levels were quantified in blood specimens using quantitative real-time PCR (qRT-PCR). Additionally, serum concentrations of interleukins (IL-32, IL-33, IL-34) and matrix metalloproteinase-9 (MMP-9) were quantified using sandwich enzyme-linked immunosorbent assay (ELISA) techniques. Results: Both NDRA and TRA groups exhibited elevated miR-26 expression and significantly increased serum levels of IL-32, IL-33, IL-34, and MMP-9 relative to healthy controls (p < 0.001). The NDRA group showed the highest cytokine and MMP-9 levels, indicating active inflammation, while the TRA group had moderately reduced levels and a greater fold increase in miR-26 expression. IL-33 and MMP-9 demonstrated the most pronounced intergroup differences, suggesting their utility as early diagnostic biomarkers. The reciprocal relationship between miR-26 and inflammatory cytokines indicates a regulatory function of it. MiR-26 expression could be downregulated during the peak of inflammation and partially restored with biotherapy treatment Conclusion: IL-33 and MMP-9 came out as prospective early diagnostic markers. The negative correlation between miR-26 and inflammatory mediators points to a regulatory, anti-inflammatory role for miR-26, which may be partially restored with treatment. These findings support the clinical utility of miR-26 and related cytokines in RA diagnosis, disease monitoring, and therapeutic targeting.